Estudo comparativo da qualidade de vida relacionada à saúde de crianças e adolescentes com doença neurológica incapacitante - Santana, Anna Flávia de Oliveira (2012)
Children and adolescents with autistic disorder (AD), cerebral palsy (CP), myelomeningocele (MM) and Down syndrome (DS) all present with impairments in their physical and psychosocial well-being compared to the healthy population. However, there is neither scientific evidence that these neurological diseases has different impacts on health-related quality of life (HRQL) of pediatric patients. The objective of this study was to identify the more vulnerable groups among these diagnoses by evaluating and comparing the HRQL of children and adolescents, from the perspective of the caregiver. Participated in this study 329 children and adolescents who comprised the group of individuals with disabling neurological diseases (DND) (n = 169 [19 with AD, 96 with CP, 30 with MM and 24 with DS]) and the group of healthy individuals (n = 160). The caregivers supplied demographic and clinical information and completed the generic HRQL questionnaire Child Health Questionnaire - Parent Form 50 (CHQ-PF50). The Cronbach s alpha coefficient was calculated to determine the reliability of the HRQL questionnaire. Comparisons were made between the scores of the CHQ-PF50 for children and adolescents (Kruskal-Wallis test) and between the demographic variables of participants and caregivers (Kruskal-Wallis or chi-square test). The median age of the patients with DNI was 8.0 years and in the healthy group was 10.0 years. There was no significant difference between the groups regarding sex. The Cronbach s alpha ranged from -0.34 to 0.97 for the CHQ-PF50. All patients with DND showed impairment in the physical summary and the impact on parent s time scale compared with healthy individuals (p < 0.05). In the psychosocial summary, the scores were lower for individuals with AD. In the physical summary, patients with CP, AD and MM had the lowest scores. The SD group had the highest number of scales and summaries with no significant difference between their scores and the scores of healthy group (p > 0.05). In conclusion, the HRQL of pediatric patients is affected to significantly different extents by the disabling neurological diseases studied. All groups of disabled children and adolescents studied exhibited decreased HRQL scores compared to the healthy population in the same age group, but the most vulnerable groups were those with AD and CP.